Критерии и показатели диагностики готовности учителей начальных классов к использованию образовательных технологий в условиях реализации - Грудупс, К.Я.; Ярочкина, Е.В. (My University, 2016)
The readiness of future primary school teachers to the use of modern learning technologies is a stable characteristic of an individual that identifies the ability to solve basic professional pedagogical tasks using new approaches in learning conditions without Polyfunctional pedagogical activity whose purpose is teaching, upbringing and development of children of primary school age.
Keywords: diagnosis; pedagogical Diagnostics; educational technology; motivational; informative criterion criterion; operational criteria